CLASSICAL SYSTEM OF SENSOR EDUCATION MARIA MONTESSORI - Дехкамбаева Зулфия Абубакировна; Солодова Юлия Валерьевна (Scholars Digest Publishing, 2023)
This article discusses the basic concept and importance of using the Montessori program in order to further develop the sensory abilities and thinking of children of early preschool age, as well as the advantages of zoning educational institutions under the M. Montessori program.
Keywords: sensory education, preschool education, self-realization, free education, pedagogy.